1987
DOI: 10.1111/j.1751-1097.1987.tb04766.x
|View full text |Cite
|
Sign up to set email alerts
|

ALL‐trans β‐CAROTENE‐5,6‐EPOXIDE IN THYLAKOID MEMBRANES

Abstract: All‐transβ‐carotene‐5,6‐epoxide has been found in the thylakoid membranes of spinach and of the cyanobacterium Synechococcus vulcanus Copeland. The epoxide was extracted from the thylakoid membranes with acetone, and was isolated by high‐performance liquid chromatography (HPLC). The structure of the epoxide was identified by means of mass, Raman, and electronic absorption spectroscopy. Changes in the amount of the epoxide, as a result of epoxidation and (apparent) de‐epoxidation reactions in the membranes, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…The fragmentation pattern (data not shown) further supports this assignment. Moreover, the same compound was found among Car oxidation products in vivo (47) and appears in chlorophyll-sensitized Car oxidation in vitro as one of the main products (27).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The fragmentation pattern (data not shown) further supports this assignment. Moreover, the same compound was found among Car oxidation products in vivo (47) and appears in chlorophyll-sensitized Car oxidation in vitro as one of the main products (27).…”
Section: Discussionmentioning
confidence: 97%
“…The chlorophyll-sensitized oxidation reactions of Car may have a biogenetic/evolutionary relevance to in vivo systems such as the enzymatic formation of ␤-carotene-5,6-epoxide, observed in leaves under high light (47,49) and more generally to the formation of epoxycarotenoids leading to the evolution of the xanthophyll cycle (8). If epoxides are indeed the early products, one might then even speculate about the recycling of such products outside the xanthophyll cycle.…”
Section: Discussionmentioning
confidence: 99%
“…7), a condition known to up-regulate At cruP transcripts (Table 1). β-carotene-5,6-epoxide has been identified in intact and isolated thylakoid membranes of spinach and T. elongatus (21). The level of β-carotene-5,6-epoxide in thylakoid membranes of spinach increased in proportion to light intensity.…”
Section: Discussionmentioning
confidence: 92%
“…5E) suggested that this compound had fewer conjugated double bonds than β-carotene. A study of the literature for rare carotenoids found in plants provided many possibilities (21)(22)(23)(24), but none seemed more likely than β-carotene-5,6-epoxide, a carotenoid that has previously been observed in photosynthetic tissues (21). β-carotene-5,6-epoxide was synthesized (25) and subjected to HPLC analysis, where it eluted at the same time and with the same spectrum as the unknown carotenoid ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation